2021
DOI: 10.1186/s12913-021-07324-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of simulation models for the long-term management of type 2 diabetes in low-and-middle income countries

Abstract: Introduction The burden of type 2 diabetes is steadily increasing in low-and-middle-income countries, thereby posing a major threat from both a treatment, and funding standpoint. Although simulation modelling is generally relied upon for evaluating long-term costs and consequences associated with diabetes interventions, no recent article has reviewed the characteristics and capabilities of available models used in low-and-middle-income countries. We review the use of computer simulation modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, it is difficult to obtain patient clinical data over extended periods of time due to logistical and privacy issues. 41 Our microsimulation is designed to simulate complex interactions between observed individual characteristics and associated health risk factors so that conclusions can be drawn about health and economic outcomes within a specific population. Combining findings from published clinical trials and original analysis, the model simulates probabilities of disease onset under alternative scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to obtain patient clinical data over extended periods of time due to logistical and privacy issues. 41 Our microsimulation is designed to simulate complex interactions between observed individual characteristics and associated health risk factors so that conclusions can be drawn about health and economic outcomes within a specific population. Combining findings from published clinical trials and original analysis, the model simulates probabilities of disease onset under alternative scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most research has been focused on producing estimates of the cost of diabetes in the short-run [8][9][10]. For example, a recent review reported the lack of studies modelling long-term economic and health effects of diabetes in low-and middle-income countries [11]. The purpose of this study was to estimate the expected cost and health outcomes in the long run for recently diagnosed diabetic patients in Chile.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas studies have appraised the application of DAMs to study diabetes interventions [ 7 – 11 ], few have focused on NP diabetes interventions in LMICs. Our study adds to this research.…”
Section: Introductionmentioning
confidence: 99%
“…Our study adds to this research. Mukonda, Cleary and Lesosky’s review on computer simulation models for type 2 diabetes in LMICs, like our present study, reports on model-based economic evaluations to support decisions in type 2 diabetes care, to assess their quality and validity [ 11 ]. However, unlike Mukonda and colleagues, we focus on DAMs for NP interventions and consider both type 1 and 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation